A study on employee engagement dimensions and its impact on organizational citizenship behaviour - Latha, Sri (Innovare Journal of Engineering and Technology, 2017)
Employee engagement is a workplace approach resulting in the right conditions for all members of an organisation to give of their best each day, committed to their organisation's goals and values, motivated to contribute to organisational success, with an enhanced sense of their own well-being. Highly-engaged employees are not only expected to work at a superior level, but also to actively apply themselves beyond formal job requirements. Thus, the concept of work behaviour that is beyond the requirement of job scope is called as organizational citizenship behaviour (OCB). Organisational Citizenship Behaviour (OCB) is a person's voluntary commitment within an organization or company that is not part of his or her contractual tasks. In this study we are trying to test the relationship between Employee Engagement and OCB, as Employee Engagement is one of the most important constructs that affect the OCB. The study focused on the dimensions of employee engagement (organizational support, career management support, Recognition and work Life Balance)as possible moderators to explain the impact and the association between employee engagement and OCB. The study is focussed at employees working in a NBFC company in Coimbatore. The research design that is used in this study is descriptive research design. The study is based on the primary data, collected from the respondents who were the employees of NBFC Company, Coimbatore. The data is collected through structured questionnaire. The sampling technique used for this study is probability sampling technique. Data Analysis was conducted using the statistical tools and the hypothesis was tested using Regression and Bi-Variate Correlation. The results of the study clearly show that employee engagement dimensions have an impact on Organization Citizenship Behaviour(OCB) and a strong amount of association exist between them.